2022
DOI: 10.3390/w14213489
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CYP4 Gene Identified in the Polychaete Sternaspis scutata and Its Transcriptional Levels along the Coasts of the Liaodong Peninsula

Abstract: Polychaetes (such as Sternaspis sculata) can biotransform polycyclic aromatic hydrocarbons (PAHs) in the environment, and the cytochrome P450 (CYP) enzyme is the key substance in this process. Here, a novel CYP gene was identified from S. sculata, a marine polychaete that is abundantly distributed along marine coasts worldwide. The full-length cDNA of the new CYP is a 1829 bp, encoding a protein of 509 amino acids. The deduced amino acid sequence of the CYP gene contains the conserved motifs of the P450 family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The purpose of this Special Issue of Water is to study the responses of individuals, communities, and even marine ecosystems to anthropogenic activity and environmental stressors, for which five original papers have been collected (Table 1). In general, these papers, based on the background of human activities and environmental pressure, have studied the molecular responses of marine polychaetes (Sternaspis scutata) to polycyclic aromatic hydrocarbons (PAHs) [8], the spatial genetic structure and diversity of the large yellow croaker (Larichthys crocea) [9], the relationship between the eDNA concentration and the biomass of the fish Acanthopagrus latus [10], the potential influencing factors of the northward expansion of warm water Doliolida (Dolioleta gegenbauri) [11], and the assessment of the quality of the benthic habitat in the intertidal zone of an estuary [12]. To study the response characteristics of marine polychaetes to environmental pollutants, Yu et al [8] identified a new Cytochrome P450 (CYP) gene from Sternaspis sculata (marine polychaetes widely distributed across the coasts of the world).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this Special Issue of Water is to study the responses of individuals, communities, and even marine ecosystems to anthropogenic activity and environmental stressors, for which five original papers have been collected (Table 1). In general, these papers, based on the background of human activities and environmental pressure, have studied the molecular responses of marine polychaetes (Sternaspis scutata) to polycyclic aromatic hydrocarbons (PAHs) [8], the spatial genetic structure and diversity of the large yellow croaker (Larichthys crocea) [9], the relationship between the eDNA concentration and the biomass of the fish Acanthopagrus latus [10], the potential influencing factors of the northward expansion of warm water Doliolida (Dolioleta gegenbauri) [11], and the assessment of the quality of the benthic habitat in the intertidal zone of an estuary [12]. To study the response characteristics of marine polychaetes to environmental pollutants, Yu et al [8] identified a new Cytochrome P450 (CYP) gene from Sternaspis sculata (marine polychaetes widely distributed across the coasts of the world).…”
Section: Introductionmentioning
confidence: 99%
“…In general, these papers, based on the background of human activities and environmental pressure, have studied the molecular responses of marine polychaetes (Sternaspis scutata) to polycyclic aromatic hydrocarbons (PAHs) [8], the spatial genetic structure and diversity of the large yellow croaker (Larichthys crocea) [9], the relationship between the eDNA concentration and the biomass of the fish Acanthopagrus latus [10], the potential influencing factors of the northward expansion of warm water Doliolida (Dolioleta gegenbauri) [11], and the assessment of the quality of the benthic habitat in the intertidal zone of an estuary [12]. To study the response characteristics of marine polychaetes to environmental pollutants, Yu et al [8] identified a new Cytochrome P450 (CYP) gene from Sternaspis sculata (marine polychaetes widely distributed across the coasts of the world). The results showed that the deduced amino acid sequence of the new CYP gene contained the conserved motif of the P450 family (FxxGxxxCxG) and the characteristic sequence of the CYP4 family (EVDTFMFEGHDTT), which showed a high degree of similarity with marine polychaete CYP4V (tentatively named SsCCYP4V).…”
Section: Introductionmentioning
confidence: 99%